BASIC CONCEPTS AND PRINCIPLES OF POWER IN ISLAMIC POLITICS - Khaldun, Rendra (UIN Mataram, 2024)
The hijrah of the Prophet Muhammad PBUH to Medina marked the birth of the initial concept of the Islamic political order by forming a plural Medina society, based on the values of justice, sovereignty, and shura. This research discusses the relationship between religion and the state in Islam, which is theoretically formulated in three main paradigms: integralistic, symbiotic, and secularistic. In addition, this article examines the basic principles of Islamic rule, such as Allah's absolute sovereignty, justice, and community participation through deliberation. The research also explores the concept of power division in Islam which includes the legislative, executive, and judiciary, as well as the typology of power between the organic approach that unites religion and the state, and the secular approach that separates them. The conclusion highlights the relevance of the Medina Charter as a reference for Islamic political principles, although it does not explicitly describe the ideals of the Islamic political order. This study identifies contemporary challenges in applying Islamic political principles amid increasingly complex global social dynamics.